Antibacterial Activity Test Of Aloe Vera (Aloe Vera) On The Growth Of Bacteries Propionibacterium acnes - Ravika Candra Ratna Kumala (LPPM Universitas dr. Soebandi, 2023)
Background: Acne is a complex disease with elements involving bacterial growth and immunity. One of the bacteria that can cause acne is Propionibacterium acnes bacteria. Aloe vera contains compounds that can inhibit bacterial growth such as saponins, flavonoids, alkaloids, and anthraquinones.Purpose: This study aims to determine the presence of antibacterial activity and antibacterial differences in 70% ethanol and ethyl acetate extracts of aloe vera meat against Propionibacterium acnes.Methods: This type of research is experimental using the maceration extraction method with 70% ethanol and ethyl acetate solvents. The sample of this research is aloe vera meat extract with a concentration of 75%, 50%, and 25%. The positive control used was tetracycline antibiotic and the negative control used distilled water. The antibacterial activity test used the pitting diffusion method with millimeter (mm) measurement.Results: The test results showed that there was antibacterial activity for ethanol extract and ethyl acetate extract. The ethanol extract formed the highest inhibition zone with a diameter of 6.77 mm at a concentration of 75%, for a concentration of 50% obtained 5.56 mm, and a concentration of 25% obtained 5.19 mm. While the ethyl acetate extract formed the highest inhibition zone with a diameter of 4.53 mm at a concentration of 75%, for a concentration of 50% obtained 3.45 mm, and a concentration of 25% obtained 2.47 mm. And there are differences in activity in the two extracts, namely 75% ethanol extract is different from 50% and 25% ethyl acetate extract, and vice versa.Conclusions: So it can be concluded that ethanol extract and ethyl acetate extract of aloe vera meat have antibacterial activity against Propionibacterium acnes. And there is a difference in antibacterial activity in 75% ethanol extract and 50% and 25% ethyl acetate extract.